ANALISIS MUATAN HIGER ORDER THINKING SKILLS (HOTS) DALAM BUKU SISWA MATA PELAJARAN IPAS - Syafitri, Anis; Riskyka, Riskyka; Anggraini, Dini Puji (Universitas Negeri Medan, 2022)
Learning outcomes in the independent curriculum in Natural and Social Sciences (IPAS) Phase B (for grades III and IV SD/MI/Package A) require that the learning carried out must be able to stimulate students to think at higher levels (HOTS ). This study discusses the analysis of HOTS content contained in IV grade IPAS textbooks for students. This research is a descriptive quantitative research. Data was collected using literature study techniques, documents, and questionnaires. Then, the percentage value of the HOTS load in the book by the data was calculated. The results obtained are interpreted to see the measurable level of thinking. There are 24 topics discussed and grouped into 8 chapters. Based on the results of the analysis of material content, creating (C6) around 12%, evaluating (C5) 12%, and analyzing (C4) 76%. While the items in the student's book, out of 33 questions scattered in the book, were found to be 12% at the C6 and C5, 73% at the C4, and 3% is C2. Overall, 98% content of the book is already contain HOTS. Based on the results, it can be assumed that the book is good for stimulating students to think at higher levels.